Gender & development - Amita Sahaya Ed; Sunita Kaistha Ed; Vibhuti Patel Ed (Empowering women worldwide series ; 12, 2011)
Papers presented at the International Conference on Gender & Development in the World of Work, held at Jhansi in March 2010.